Post-Mortem Interval Estimation Using Newton’s Law of Cooling and the Henssge Model - NORAHIM, NUR AINA UMIRA; Ibrahim, Norzuria (Enhanced Knowledge in Sciences and Technology, 2026)
The estimation of post-mortem interval (PMI) is an essential part of the forensic investigation, as it helps to reconstruct events related to the death and make decisions about medico-legal matters. The use of temperature-based techniques, particularly the approaches that are based on algor mortis, is often used in the early post-mortem phase due to its quantitative and supposedly objective nature. However, the accuracy of PMI estimation still happens to be an issue, because the cooling of the body is regulated by environmental factors and personal physiological factors. This study aimed at comparing the performance of the Newton’s Law of Cooling, and the Henssge approach in estimating PMI under controlled conditions over a range of observation times. Both method were used in documented post-mortem temperature data, and PMI estimates were tested at both the short and long post-mortem timeframes. An algorithmic implementation was applied to obtain the PMI estimates and the precision of every technique was measured in terms of absolute error and mean absolute error (MAE). Moreover, this study has conducted scatter plot analyses to examine the correlation between the  error in estimations and the various selection factors related to the correction, and anthropometric variables. The results showed that Henssge method is slightly more accurate in the early post-mortem period but Newton Law of Cooling is more consistent and less prone to increase its errors over the longer post-mortem periods. Therefore, these results imply that the accuracy of temperature-based PMI estimates changes with the post-mortem interval, and rather than depending entirely on one method, the expected time since death should be used to guide method selection.